2021
DOI: 10.1111/ijcp.14061
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary inflammatory index with sleep quality and obesity amongst iranian female students: A cross‐sectional study

Abstract: Background: Overweight, obesity and lack of sleep quality as inflammatory states are the common problems amongst college students and the Association of Dietary Inflammatory Index (DII) with these problems amongst this population is unknown.We aimed to evaluate the relationship of the DII with obesity and sleep quality amongst Iranian female students. Methods:The present cross-sectional study was conducted on 249 female college students. The Dietary Inflammatory Index (DII) was calculated using a valid and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Here, the highest category of DII (i.e., most proinflammatory) was associated with lower likelihood of having adequate sleep quality and in particular impaired sleep latency, and even more strongly after adjusting for the Mediterranean diet adherence underscoring that both DII and the Mediterranean diet were acting through a common denominator that may be inflammation [ 124 ]. Similar associations between higher DII scores and poor sleep quality [ 125 ] or daytime dysfunction [ 126 ] were observed in small cohorts of college students. In another study conducted in OSA patients the DII was positively associated with apnea severity and daytime sleepiness, and predicted rapid eye movement latency [ 127 ].…”
Section: Potential Mechanisms Underlying the Mediterranean Diet Effec...mentioning
confidence: 52%
“…Here, the highest category of DII (i.e., most proinflammatory) was associated with lower likelihood of having adequate sleep quality and in particular impaired sleep latency, and even more strongly after adjusting for the Mediterranean diet adherence underscoring that both DII and the Mediterranean diet were acting through a common denominator that may be inflammation [ 124 ]. Similar associations between higher DII scores and poor sleep quality [ 125 ] or daytime dysfunction [ 126 ] were observed in small cohorts of college students. In another study conducted in OSA patients the DII was positively associated with apnea severity and daytime sleepiness, and predicted rapid eye movement latency [ 127 ].…”
Section: Potential Mechanisms Underlying the Mediterranean Diet Effec...mentioning
confidence: 52%
“…81 Interestingly, individuals in the fourth quartile (most inflammatory diets) had significantly greater intakes of monosaturated fatty acids and saturated fats compared with individuals with the most anti-inflammatory diets (low DII scores). 81 In our updated review, we included several new studies that further strengthened evidence from 2019, 24 in particular in men, and several large studies adjusted the relationships between DII and obesity for energy intake. Most studies employed BMI and body weight as obesity measures rather than adiposity.…”
Section: And Obesitymentioning
confidence: 92%
“…A study in 249 Iranian women investigated the inflammatory potential of diet and its effect on sleep and obesity. 81 The authors found that high DII (as a continuous variable) was significantly negatively associated with BMI, weight, and WC, although these did not reach significance in the adjusted model. 81 Interestingly, individuals in the fourth quartile (most inflammatory diets) had significantly greater intakes of monosaturated fatty acids and saturated fats compared with individuals with the most anti-inflammatory diets (low DII scores).…”
Section: And Obesitymentioning
confidence: 94%
See 1 more Smart Citation
“… 14 Besides, some literatures have shown that higher DII scores were related to poorer sleep quality. 15 , 16 However, few studies have evaluated the relationship among DII, sleep quality, and the risk of CVD. Therefore, we aim to investigate whether DII plays a mediating role in the relationship between sleep quality and CVD risk.…”
Section: Introductionmentioning
confidence: 99%